ANALISIS WEBSITE, YOUTUBE, INSTAGRAM TERHADAP CITRA ORGANISASI MELALUI KEPUASAN KONSUMEN PADA DINDIKPORA KOTA YOGYAKARTA - Khusna Indah Wijayanti; Muinah Fadhilah; Henny Welsa (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
The purpose of this study was to analyze the influence of websites, YouTube, and Instagram on organizational image through consumer satisfaction. The research method used in this study is a quantitative method. The sample used was the teacher of DINDIKPORA with a total of 100 respondents. Methods of data collection using a questionnaire with probability sampling technique. The data analysis technique used descriptive analysis, inferential analysis and path analysis with SmartPLS 3.2.9 analysis tool. The results showed that the website had a positive and significant effect on consumer satisfaction, YouTube had no effect on consumer satisfaction, Instagram had a positive and significant effect on consumer satisfaction, the website had no effect on organizational image, YouTube had no effect on organizational image, Instagram had no effect on organizational image, consumer satisfaction has a positive and significant effect on organizational image, consumer satisfaction is unable to mediate the relationship between website and organizational image, consumer satisfaction is unable to mediate the relationship between YouTube and organizational image, and consumer satisfaction is unable to mediate the relationship between Instagram and organizational image